Penentuan Bantuan Buku Perpustakaan Daerah Di Dinas Perpustakaan Dan Kearsipan Kabupaten Asahan Dengan Metode SAW - Wendy Rizki Ferdana; Bachtiar Efendi; Tika Christy (LPPM STMIK Royal Kisaran, 2022)
Abstract: The library is one of the information centers that is very close and familiar to the community. Apart from the information center, the library is also a source of knowledge, research, and various other services. Then process, preserve, maintain and maintain the entire library book collection in order to keep it in good condition, intact, fit for use and not easily damaged and present this information to users for use and empowerment. Along with the increasing participation of the community to assist the government in the implementation of increasing interest and reading culture as well as a source of knowledge, many libraries have been established in the Asahan Regency area. The establishment of regional libraries to accelerate the increase in interest and reading culture as well as a means of sources of knowledge. In achieving the target of developing regional libraries in the region in Asahan Regency, the Library and Archives Office also has a book distribution assistance program, with the target of regional libraries in the Asahan Regency area, which will be targeted as beneficiaries of assistance, and each regional library is not yet known for certain books. what is in demand in each area of Asahan Regency. In selecting libraries and determining the distribution of books that will be donated to the library requires criteria as a comparison for each library in Asahan Regency, so that the distribution of book aid is right on target. Keywords: Distribution book; SAW Method. Abstrak: Perpustakaan adalah salah satu pusat informasi yang sangat dekat dan akrab dengan masyarakat. Selain pusat informasi, perpustakaan juga merupakan sumber ilmu pengetahuan, penelitian, serta berbagai layanan jasa lainnya. Seiring dengan meningkatnya peran serta masyarakat untuk membantu pemerintah dalam pelaksanaan peningkatan minat dan budaya baca serta sebagai sarana sumber ilmu pengetahuan, maka telah banyak berdiri perpustakaan di daerah Kabupaten Asahan. Berdirinya perpustakaan daerah untuk mempercepat peningkatan minat dan budaya baca serta sebagai sarana sumber ilmu pengetahuan. Dalam pencapaian target pengembangan perpustakaan daerah di wilayah di Kabupaten Asahan, maka Dinas Perpustakaan dan Arsip juga memiliki program bantuan pemberian buku, dengan sasaran perpustakaan daerah dalam Wilayah Kabupaten Asahan, yang akan ditetapkan menjadi sasaran penerima bantuan, dan setiap perpustakaan daerah belum diketahui secara pasti buku apa saja yang diminati disetiap daerah Kabupaten Asahan. dalam memilih perustakaan dan menentukan distribusi buku yang akan disumbangkan kepada perpustakaan memerlukan kriteria-kriteria sebagai perbandingan setiap perpustakaan yang ada di Kabupaten Asahan, sehingga dalam distribusi bantuan buku tepat sasaran. Kata kunci: Pemberian Bantuan Buku; Metode SAW.